2023
DOI: 10.1021/acs.analchem.3c00223
|View full text |Cite
|
Sign up to set email alerts
|

Expedited Evaluation of Conformational Stability–Heterogeneity Associations for Crude Polyclonal Antibodies in Response to Conjugate Vaccines

Abstract: Conjugate vaccines have been demonstrated to be a promising strategy for immunotherapeutic intervention in substance use disorder, wherein a hapten structurally similar to the target drug is conjugated to an immunogenic carrier protein. The antibodies generated following immunization with these species can provide long-lasting protection against overdose through sequestration of the abused drug in the periphery, which mitigates its ability to cross the blood–brain barrier. However, these antibodies exhibit a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Data in Figure S2 clearly show that the full width at half-maximum (fwhm) values of pAbs are significantly higher than that of mAb, suggesting much higher heterogeneity for pAbs. The observed increment in microheterogeneity of pAbs should be linked to the elevated sequence variation in the antigen-binding domain and the glycosylation at the CH2 domain during antibody production . Overall, native IM-MS measurements initially reveal varied degrees of difference in chemical composition, or molecular microheterogeneity, for different therapeutic pAbs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data in Figure S2 clearly show that the full width at half-maximum (fwhm) values of pAbs are significantly higher than that of mAb, suggesting much higher heterogeneity for pAbs. The observed increment in microheterogeneity of pAbs should be linked to the elevated sequence variation in the antigen-binding domain and the glycosylation at the CH2 domain during antibody production . Overall, native IM-MS measurements initially reveal varied degrees of difference in chemical composition, or molecular microheterogeneity, for different therapeutic pAbs.…”
Section: Resultsmentioning
confidence: 99%
“…The observed increment in microheterogeneity of pAbs should be linked to the elevated sequence variation in the antigenbinding domain and the glycosylation at the CH2 domain during antibody production. 7 Overall, native IM-MS measurements initially reveal varied degrees of difference in chemical composition, or molecular microheterogeneity, for different therapeutic pAbs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis indicated that both the sequence variations in the antigen-binding domain (Fab) and glycosylation at the CH2 domain (Fc) played simultaneous roles in the observed molecular microheterogeneity. These variations may have significant implications for the conformational stability and binding efficacy of the antibodies towards haptens [ 39 ]. In summary, this methodology facilitates the development of vaccines capable of eliciting an immune response specifically tailored to the target drug.…”
Section: Conjugate Vaccinesmentioning
confidence: 99%